2012
DOI: 10.1073/pnas.1110620109
|View full text |Cite
|
Sign up to set email alerts
|

Release of dendritic cells from cognate CD4+T-cell recognition results in impaired peripheral tolerance and fatal cytotoxic T-cell mediated autoimmunity

Abstract: Resting dendritic cells (DCs) induce tolerance of peripheral T cells that have escaped thymic negative selection and thus contribute significantly to protection against autoimmunity. We recently showed that CD4 + Foxp3+ regulatory T cells (Tregs) are important for maintaining the steady-state phenotype of DCs and their tolerizing capacity in vivo. We now provide evidence that DC activation in the absence of Tregs is a direct consequence of missing DC-Treg interactions rather than being secondary to generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…This genetic approach showed that steady-state antigen presentation by DCs induces a profound and irreversible unresponsiveness in CD8 + T cells; this includes the upregulation of the inhibitory molecules programmed cell death protein 1 (PD1) and cytotoxic T lymphocyte antigen 4 (CTLA4) on CD8 + T cells 20 . The tolerogenic capacity of DCs in this context was enforced by MHC class II-dependent interactions with T Reg cells, and MHC class II-deficient DCs were proposed to induce CD8 + T cell-mediated autoimmunity 21 . Thus, DCs can induce peripheral T cell tolerance to immunodominant antigens that are expressed at high levels.…”
Section: The Role Of Dcs In Immune Tolerancementioning
confidence: 99%
“…This genetic approach showed that steady-state antigen presentation by DCs induces a profound and irreversible unresponsiveness in CD8 + T cells; this includes the upregulation of the inhibitory molecules programmed cell death protein 1 (PD1) and cytotoxic T lymphocyte antigen 4 (CTLA4) on CD8 + T cells 20 . The tolerogenic capacity of DCs in this context was enforced by MHC class II-dependent interactions with T Reg cells, and MHC class II-deficient DCs were proposed to induce CD8 + T cell-mediated autoimmunity 21 . Thus, DCs can induce peripheral T cell tolerance to immunodominant antigens that are expressed at high levels.…”
Section: The Role Of Dcs In Immune Tolerancementioning
confidence: 99%
“…MHC class II–impotency feedback does not exist in MARCH1-deficient B cells (although MARCH1-deficient B cells also overexpress MHC class II molecules) (211), pDCs (95), or FLT3-L-cultured BMDCs (217), indicating that unique in vivo requirements dictate MHC class II–impotency feedback on cDC functions. The mechanism of this feedback could involve cell-intrinsic or -extrinsic suppression of inappropriate MHC class II high DCs, perhaps transduced by MHC class II molecules (219, 220). cDCs of MARCH1-deficient mice may be analogous to hypothetical “exhausted” DCs (221223) or to endotoxin tolerant macrophages, which are unresponsive to endotoxin stimulation partly as a result of altered NF-κB activation, chromatin modifications, and upregulated expression of negative regulators of signal transduction (179, 224, 225).…”
Section: Mhc Class II Molecules and Dendritic Cell Functionsmentioning
confidence: 99%
“…Ablation of DCs in donor marrow leads to CD4 + T cell infiltration into multiple peripheral organs in syngeneic WT recipients (36), and bone marrow with DCs that are defective in cognate CD4 + T-cell recognition resulted in impaired peripheral tolerance, with fatal CD8 + T cell cytotoxicity in syngeneic WT recipients (37). Here we identified DCs as the primary hematopoietic cells expressing MHCII required for selection and/or “licensing” of functional IMP CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%